POTENSI BIJI NANGKA DAN BIJI SAGA SEBAGAI BAHAN BAKU PEMBUATAN TEMPE KOMPLEMENTASI - Mardina '; Yusmarini '; Rudianda Sulaeman (Universitas Riau, 2012)
This study aims to evaluate the quality of tempeh complementation from jackfruit seeds and saga.This research carried out experiments using Complete Randomized Design (CRD) to six treatment that is:NS0 (100% soy as a control); NS1 (90 jackfruit seeds : 10 saga); NS2 (80 jackfruit seeds : 20 saga); NS3(70 jackfruit seeds : 30 saga); NS4 (60 jackfruit seeds : 40 saga) and NS5 (50 jackfruit seeds : 50 saga).The results showed that the complementation of jackfruit seeds and saga significantly affect the moisturecontent, ash content, protein content, fat content, color, aroma, taste and overall assessment and theyhave been conformed tempeh ISO standards, except fat content. Jackfruit seeds and saga complementationNS4 (60 jackfruit seeds : 40 saga) will produce a better tempeh with moisture content 61.53%, ash content0.93%, protein content 28.87%, fat content 5.98%, white color, less-typical tempeh aroma, tastes a goodand overall assessment is less preferred by the panelists.Key words : Jackfruit seeds, saga, tempeh, fermentation, Rhizopus sp.